Study of Potential Interactions with Oral Antidiabetic Drugs in Patients at the Outpatient Department of dr. M. Yasin Hospital, Bone Regency - Puji Kurniawati Rahman; Fitria; Teguh Setiawan Wibowo (PT. Banjarese Pacific Indonesia, 2024)
Diabetes Mellitus (DM) is a metabolic disorder characterized by an increase in blood glucose levels above the normal limit. One thing that can influence the effectiveness of treatment therapy for Diabetes Mellitus patients is the possibility of drug interactions. This research is a type of descriptive research which aims to determine the possibility of oral antidiabetic drug interactions in patients at the Outpatient Installation of Dr.M.Yasin Hospital, Bone Regency. Research data collection was carried out by taking secondary data from outpatient prescriptions at the Dr. The data used is that the patient's prescription is collected and then identified whether it meets the inclusion and exclusion criteria. If a prescription has been obtained that meets the criteria, the prescription is recorded. The next step is to assess the possibility of drug interactions based on the application and drug interaction guidebook. From the results of the study, it was concluded that there is a possibility of oral antidiabetic drug interactions occurring in patients at the Outpatient Installation at Dr.M.Yasin Hospital, Regency. Bone from December 2014 to August 2015 with a percentage of 55.3% of the 38 research sample prescription sheets.